The Strategic Role of School Principals in Realizing Student-Centered Learning - Hariyadi, Ahmad (CV. Bimbingan Belajar Assyfa, 2024)
In the dynamic era of 21st-century educational transformation, developing students' critical thinking, creativity, and independence has become a top priority, where student-centered learning models are viewed as the most effective and creative strategies to enhance these competencies. The background of this research is driven by the fact that while curricula continue to evolve, instructional leadership often fails to optimally evaluate teaching effectiveness and its impact on student engagement and the holistic development of cognitive, affective, and psychomotor domains. This study aims to analyze the strategic contribution of school principals in creating an innovative learning ecosystem within the framework of the Merdeka Curriculum. The method employed is a qualitative approach using a literature review design and bibliometric analysis with VOSviewer and Publish or Perish software to map publication trends and data collection techniques based on academic documents. The results indicate that the principal's leadership has a significant positive impact on learning quality through providing resources and motivation to teachers, where scaffolding variables in managerial assistance serve as a key determinant of success; however, it was found that providing physical facilities alone has no effect without a shift in educators' mindsets. In conclusion, the principal's role as a primary driver is crucial for the sustainability of educational innovations that focus on students' unique potential.